A multicenter all-inclusive prospective study on the relationship between glycemic control markers and maternal and neonatal outcomes in pregnant women. (2nd October 2021) - Zhang, Xiaoming; Wei, Yumei; Fan, Ling; Zhao, Yangyu; Li, Yufeng; Liu, Yanjun; Lu, Juming; Ji, Linong; Yang, Huixia
Abstract: Objective: Pregnant women afflicted with gestational diabetes mellitus (GDM) and diabetes mellitus (DM) are prone to both maternal and neonatal complications. Due to this, it is of importance to sustain a strict glycemic control during this time. Unfortunately, there is a lack of evidence-based medical research for the control criteria during pregnancy. Therefore, to develop better method of glycemic control for pregnant women, we conducted a multicenter all-inclusive prospective study to investigate the association between glycemic control markers and maternal and neonatal outcomes. Research design and methods: Four hundred fifty-two women were included in the study. Fasting blood glucose (FBG), HbA1c and glycated albumin (GA), and ferritin levels were measured at different gestational periods and compared to the pregnancy outcomes. Results: The reference interval of GA and HbA1c was determined in Trimester I, II, III: 11.0–16.3%, 10.1–15.2%, and 9.5–14.6%, and 4.8–5.7%, 4.4–5.4%, and 4.7–5.8%, respectively. It was found that at the later stages of pregnancy, there was a reduction in ferritin levels and increase in HbA1c levels. Only in the GDM group, it was noticed that the frequency of total neonatal and maternal complications were significantly higher on comparison with the normal group (30.1 vs. 18.4%, p = . 017 and 21.0% vs. 12.0%, p = . 031, respectively). For the frequency of cesarean section and macrosomia in GDM group, GA > 15.69% group was significant higher compared to those of GA ≤ 15.69% group ( p = . 021 and p = . 001, respectively). For HbA1c, no significant differences were observed. Conclusions: A reference interval of HbA1c and GA was developed for Chinese pregnant women. We found that the GDM group had a higher frequency of neonatal and maternal complications. As only GA levels and not HbA1c, were associated with cesarean section and macrosomia in GDM, we hypothesize that GA could be an appropriate glycemic control marker for pregnant mothers.